2022
DOI: 10.3892/mmr.2022.12735
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA GAS5 promotes pyroptosis in COPD by functioning as a ceRNA to regulate the miR‑223‑3p/NLRP3 axis

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by irreversible and progressive airflow limitation and encompasses a spectrum of diseases, including chronic obstructive bronchitis and emphysema. Pyroptosis is a unique form of inflammatory cell death mediated by the activation of caspase-1 and inflammasomes. The long non-coding RNA (lncRNA) growth arrest-specific 5 (GAS5) is a well-documented tumor suppressor, which is associated with cell proliferation and death in various diseases. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…22 lncRNA GAS5 promotes pyroptosis in COPD by functioning as a ceRNA to regulate the miR-223-3p/ NLRP3 axis. 23 Many studies have also confirmed the expression profile of lncRNA in the lung tissues of non-smokers and smokers, with or without COPD, 24 which will help to find early biomarkers and treatment targets associated with COPD. 13 Differential gene expression of LINC00599 has been reported in current smokers as compared to former smokers, and up-regulation of LINC00599 was indicated in response to cigarette smoking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…22 lncRNA GAS5 promotes pyroptosis in COPD by functioning as a ceRNA to regulate the miR-223-3p/ NLRP3 axis. 23 Many studies have also confirmed the expression profile of lncRNA in the lung tissues of non-smokers and smokers, with or without COPD, 24 which will help to find early biomarkers and treatment targets associated with COPD. 13 Differential gene expression of LINC00599 has been reported in current smokers as compared to former smokers, and up-regulation of LINC00599 was indicated in response to cigarette smoking.…”
Section: Discussionmentioning
confidence: 93%
“…22 lncRNA GAS5 promotes pyroptosis in COPD by functioning as a ceRNA to regulate the miR-223-3p/NLRP3 axis. 23 Many studies have also confirmed the expression profile of lncRNA in the lung tissues of non-smokers and smokers, with or without COPD, 24 which will help to find early biomarkers and treatment targets associated with COPD. 13…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, another study on patients with chronic obstructive pulmonary disease by Rubing Mo and collaborators found that LPS induces lncRNA GAS5 expression and release of IL-2, IL-6, IL-10, and TNF-α. Additionally, the upregulation of GAS5 promoted cell death and inhibited proliferation in the MRC-5 cell line, suggesting that lncRNA GAS5 is related to promoting pyroptosis in that kind of patient [ 22 ]. In this line of information, lncRNA HOTAIRM1 has been described to play a critical role in inflammatory and allergic response; one study led by Lihua Li and collaborators found that HOTAIRM1 are implicated in allergic rhinitis by promoting differentiation of T helper type 9 cells through miR-148a-3p interaction [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RAD51-AS1 was discovered to be associated with the NF-κB pathway in inflammatory bowel disease (Papoutsopoulou and Campbell, 2021), which could account for the upregulation expression of IL-6, TNF-α, and CCL2. GAS5 targets two crucial cytokines (IL-10 and TNF-α), and the possible mechanisms may be that upregulating GAS5 expression decreases miR-223-3p expression, which increases NLRP3 expression levels and promotes pyroptosis (Mo et al, 2022). GAS5 also downregulates miR-23a-3p levels, which can inhibit the release of inflammatory substrates by inhibiting the TLR4/TNF-α/IL-10 signaling pathway (Gao and Huang, 2021).…”
Section: Cytokine Stormmentioning
confidence: 99%